The Effect of Content Marketing and Brand Image of Skintific Products on Purchase Intention, with Trust as a Moderator (Case Study: Consumers TikTok Shop in Jakarta) - Ainy, Farah Nurul; Reza, Bobby; Darnis, Rahmi (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This research investigates how Content Marketing and Brand Image influence Purchase Intention among Jakarta-based Skintific consumers on TikTok Shop, specifically examining the moderating role of Trust. The research sample comprises 150 respondents spanning various age groups and educational backgrounds. Utilizing SmartPLS for data analysis, the study revealed that while Content Marketing fails to yield a significant positive impact on Purchase Intention, both Brand Image and Trust emerge as powerful, significant drivers of consumer intent. The study also highlights that the respective impacts of Content Marketing and Brand Image on Purchase Intention are significantly contingent upon the level of consumer Trust. Overall, the results emphasize that consumer trust is an essential factor in strengthening Purchase Intention toward Skintific products on TikTok Shop.